Properness and topological degree for nonlocal integro-differential systems - Apreutesei, Narcisia C.; Volpert, Vitaly A. (Topological Methods in Nonlinear Analysis, 2016)
Reaction-diffusion systems of equations with integral terms are studied. Essential spectrum of the corresponding linear operators is determined and the Fredholm property is studied. Properness of nonlinear operators is proved and topological degree is constructed.